OPTIMALISASI PERAN DANA KUR (KREDIT USAHA RAKYAT) DALAM MEMBERANTAS PRAKTEK RENTENIR BANK EMOK UNTUK MENINGKATKAN KINERJA UMKM DI DESA BOJONGSARI - Afisa, Hilda Nur; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Micro businesses included in the small and medium-sized micro enterprises (MSMEs) have a fairly important role in building the economy in Indonesia. Evidently at the time of the economic crisis hit Indonesia, the government relied heavily on the role of MSMEs to minimize the negative impact of the economic crisis. MSMEs are stand-alone productive business units, conducted by individuals or business entities in all sectors of the economy. Based on the results of research conducted on the people of Karangtanjung Village, especially msme business actors Paguyuban Macan Berdikari in getting real results that more than 80% of the village community is very dependent on the loan of emok bank (loan shark lending practices) which in this practice the interest given is so large that it chokes the people in the village. To overcome this, it is necessary to have special counseling related to the impact of business capital lending to emok banks, so that the public will be aware of how cruel the practices carried out by loan sharks in the provision of interest. A business will grow when the loan of capital to advance the business is on target. Because borrowing money to a bank is the first step of a bankruptcy. Therefore, to minimize the occurrence of unwanted things, people need to realize that borrowing capital to state-owned banks is the right thing.